The impact of speech rate reduction techniques on the listening comprehension performance of Egyptian high school students - Ibrahim, Ghada Abdul-moneim (AUC Knowledge Fountain, 2012)
The speech rate (SR) of the recorded aural native input has been recurrently reported by EFL listeners worldwide as being the major obstacle to achieve successful listening comprehension (LC). To investigate the efficacy of natural rate reduction techniques in facilitating LC, this study was designed to compare and contrast the immediate effect(s) of exposing two intact classes (n=46) of Egyptian high school students enrolled in the International General Certificate of Secondary Education (IGCSE) to two SR reduction techniques. The first technique was the deliberate articulation (DA), and the second was inserting three-second pauses at T-unit boundaries. The dependent variables were the students' LC task scores on the one hand, and their perceptions of the slow speeds appropriateness to their LC needs, on the other hand. LC proficiency was considered as a moderating variable. A Control group (n=26) was included to collect baseline data on these students' LC performance in the "normal" SRs adopted in Cambridge exams. A mixed design approach was followed in collecting data. Five sets of LC task scores were gathered in five weeks. During the 1st, 3rd and 5th weeks, the experimental classes completed the LC tasks in the normal speed (NS) condition. In the 2nd and the 4th weeks, the experimental classes performed their LC tasks while listening to texts modified according to the two techniques under investigation. This design was meant to allow each of these two classes to experience the two reduced SR conditions. Triangulation of data collection tools was achieved. Thus, beside task scores and class observations, retrospective semi-structured interviews were held with 14 students representing three LC proficiency levels immediately after each of the five tasks to examine in depth the interaction between the listeners' LC proficiency level and their perceptions of the reduced SRs appropriateness. SPSS analyses of significance of variance (one-way ANOVA and independent t-tests) of mean scores showed a statistically significant drop in LC scores in the reduced SR conditions compared to the normal ones. Further, the interviewees' input clarified the observed discrepancy between perceptions of improved overall understanding and poor task performance. Although both techniques provided the participants with added processing time to deduce meanings, and to read questions thoroughly before listening, the reduced SRs interfered with the introspective task management leading to concentration breakdown and feelings of boredom. Despite this interference, a number of intermediate and all of the low-level interviewees received improved task scores, and reported facilitated LC. One implication of the results is that English as a Foreign Language learners (EFLs) of advanced, intermediate and low LC proficiency are recommended to be instructed in "rapid speech phonology" (Cauldwell, 2002) by a variety of SR reduction techniques to develop sound LC bottom-up skills before their exposure to the spontaneous native talk.